2007
DOI: 10.1203/pdr.0b013e3181598836
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Turbulence in Children—Age and Heart Rate Relationships

Abstract: Heart rate turbulence (HRT) is a chronotropic response of the sinus heart rhythm to ventricular premature beat (VPB). Children show decreasing heart rate together with the maturation of the autonomic nervous system. The aim of the research was to assess the relationship between HRT parameters, age, and heart rate and time domain heart rate variability (HRV) parameters in healthy children. Twenty-four-hour ECG Holter recording was performed on 398 healthy children. The mean RR interval preceding VPB, number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Since both HRV and IS could be influenced by the level of physical fitness [ 52 , 57 ], participants were asked to report whether they regularly exercise (yes or no) and list sportive activities. In addition, previous research has shown that pubertal development has an impact on cardiac contractility [ 58 ] and HRV [ 59 , 60 ]. Furthermore, the influence of pubertal development on HRV should be considered, certainly in the context of parental psychopathology [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Since both HRV and IS could be influenced by the level of physical fitness [ 52 , 57 ], participants were asked to report whether they regularly exercise (yes or no) and list sportive activities. In addition, previous research has shown that pubertal development has an impact on cardiac contractility [ 58 ] and HRV [ 59 , 60 ]. Furthermore, the influence of pubertal development on HRV should be considered, certainly in the context of parental psychopathology [ 48 ].…”
Section: Methodsmentioning
confidence: 99%
“…Increasing age is associated with a decrease in HRT (61), which is consistent with similar reports concerning most measures of autonomic control. Interestingly, however, pre-pubertal children have lower TS than children during puberty, paralleling maturation of the autonomic nervous system (62).…”
Section: Figure 3 Normal Post-ectopic Blood Pressure and R-r Intervalmentioning
confidence: 98%
“…RSA may serve as a downstream marker of regulatory ability related to cortical development or dysfunction (Beauchaine 2015). Evidence from TD populations implicates developmental effects on ANS measures such as RSA that occur during puberty (Tanaka et al 2000; Kowalewski et al 2007; Jarrin et al 2015) and correlate with age, with the greatest effects in the adolescent epoch beginning at the onset of puberty (Shahrestani et al 2015). RSA studies in TD populations suggest ANS stabilization that occurs between the ages of four and five, and then again during adolescence with the onset of puberty (Pitzalis et al 2000; Woodall and Matthews 1993), followed by a gradual decline with aging (De Meersman 1993; Jennings and Mack 1984).…”
Section: Introductionmentioning
confidence: 99%